First Maximum Sustainable Yield advice for the Nephrops norvegicus stocks of the Northwest Iberian coast using stochastic Surplus Production model in Continuous Time (SPiCT) - González Herraiz, Isabel; Vila, Yolanda; Cardinale, Massimiliano; Berg, Casper W.; Winker, Henning; Azevedo, Manuela; Mildenberger, Tobias K.; Kokkalis, Alexandros; Vázquez Vilamea, A. Armando; Morlán, Roberto; Somavilla, Raquel; Pennino, Maria Grazia (Frontiers in Marine Science, 2023)
The assessment of the status of fisheries resources is pivotal due to the importance of marine resources in global food security and to halt the ongoing decline in marine biodiversity. Norway lobster (Nephrops norvegicus) is one of the most valuable resources in the Northeast Atlantic. However, overfishing has caused the decline of several Nephrops stocks over the last decades, particularly in the Nephrops Functional Units (FUs) 25 (NW Spain), 26-27 (NW Spain and North Portugal) and 31 (Cantabrian Sea, North Spain). Since 2003, the information provided by the very low level of landings and fishing effort of these three stocks was insufficient to carry out an adequate analytical assessment, so the base of the assessment has been the trends from commercial catch per unit effort (CPUE). The objective of this study was to carry out the first assessment of these three stocks with an analytical MSY-based model. A review of the available data was made and the stochastic Surplus Production Model in Continuous Time (SPiCT) was fitted for each FU. The results indicate an extremely low biomass for FUs 25 and 26-27 since the mid-nineties well below the reference points. For FU 31, on the other hand, estimated biomass is larger. Our findings also identified long-term temporal and spatial changes in the population dynamic of Nephrops in the Northwest Iberian coast. The results were compare with those obtained in the same stocks with other data-limited methods. Also the role of abiotic factors on the observed dynamic of the stocks was explored. The results of this study are not only relevant for the sustainable exploitation of Norway lobster stocks off the Northwest Iberian coast but provide valuable insights into the suitability and limitations of production models for the assessment of crustacean stocks in general.